PENGARUH PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SDN 06 PONTIANAK SELATAN - Huda, Muhammad Nurul; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The purpose of this study is to investigate how the Cooperative Integrated Reading and Composition (CIRC) model affects the reading comprehension skills of SDN 06 South Pontianak fifth-grade pupils. The study was carried out utilizing a quasi-experimental design and an experimental methodology. All fifth-grade pupils, split into two groups, made up the population. Twenty-four students from class VB and twenty-five students from class VA were included in the sample. An essay test with 12 questions served as the research tool, and data was gathered utilizing a measuring approach. According to the data analysis, the experimental class's average final test score was 79.6, whereas the control group's average score was 71.25. Hypothesis testing using the t-test resulted in a calculated t-value of 2.910, with a degree of freedom (df) of 47 (25+24-2) and a significance level of Î± = 5%, where the critical t-value was 2.012. Since ð‘¡count > ð‘¡table, the alternative hypothesis (Ha) was accepted. Furthermore, it was determined that the effect size (d) was 0.83. These results show that fifth-grade students at SDN 06 South Pontianak's reading comprehension abilities are greatly impacted by the use of the Cooperative Integrated Reading and Composition (CIRC) model in Indonesian language instruction.